Infragravity waves and cross-shore motion–a conceptual study - Bondehagen, Andreas; Kalisch, Henrik; Roeber, Volker (Frontiers in Marine Science, 2024)
It is widely known that Infragravity (IG) waves induce cross-shore fluid motion in the nearshore, and multiple recent observational studies have identified IG waves as the dominant factor for a range of nearshore processes such as particle drift in the surf zone, transport of suspended sediment and river plume oscillations. While it is clear that the underlying orbital motion linked to IG wave excursions correlates with IG wave periods, the exact relation between the IG wave amplitude and the strength of the cross-shore motion has not been investigated in great detail. In the present contribution, we aim to quantify the cross-shore motion as a function of the IG wave amplitude. Indeed, it is shown that IG waves of even the most minute amplitude induce a large horizontal movement of particles, and the cross-shore movement is often several orders of magnitude larger than the particle movement induced by ordinary gravity waves. The results hold across a number of situations including monochromatic waves, sea states given by a spectrum as well as nonlinear waves with and without strong bathymetric forcing.